2015
DOI: 10.1021/cs501542n
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Pathway in the Electrochemical Reduction of CO2 on RuO2

Abstract: RuO 2 has been reported to reduce CO 2 electrochemically to methanol at low overpotential. Herein, we use density functional theory (DFT) to gain insight into the mechanism for CO 2 reduction on RuO 2 (110). We investigate the thermodynamic stability of various surface terminations in the electrochemical environment and find CO covered surfaces to be particularly stable, although their formation might be kinetically limited at mildly reducing conditions. We identify the lowest free energy pathways for CO 2 red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
163
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 144 publications
(171 citation statements)
references
References 41 publications
6
163
0
2
Order By: Relevance
“…The latter resulti si na greement with previous findings by Karamad et al [29] The calculated methanol onset potentials presented here take into account the potential requirement for OH* removal neededt ok eep the active site availablef or CO 2 reduction.A ll the calculated onsetp otentials are lower than or equal to the OH* removal potentialfor strongly bindings urfaces. Here it is seen that the palladium/platinum oxide overlayer shows thermodynamically limitedH 2 COOH* formation, whereas OH* removal is limiting for the Mo/Nb/Ta/Ti-containing overlayers.…”
Section: Methanol Productionsupporting
confidence: 89%
See 4 more Smart Citations
“…The latter resulti si na greement with previous findings by Karamad et al [29] The calculated methanol onset potentials presented here take into account the potential requirement for OH* removal neededt ok eep the active site availablef or CO 2 reduction.A ll the calculated onsetp otentials are lower than or equal to the OH* removal potentialfor strongly bindings urfaces. Here it is seen that the palladium/platinum oxide overlayer shows thermodynamically limitedH 2 COOH* formation, whereas OH* removal is limiting for the Mo/Nb/Ta/Ti-containing overlayers.…”
Section: Methanol Productionsupporting
confidence: 89%
“…[25,26] However,i th as been suggested that metal catalysts can be selective for formic acid production over HER if OCHO*i st he reactioni ntermediate instead of COOH* because of the lack of scaling between H* and OCHO*. Following previous theoreticalw ork on the CO2RR mechanism for rutile oxide catalyst, [29] we limit our study to ar educed reaction network with only C 1 products and intermediates that bind through O. This providesadditional scope to suppresst he HER activity over CO2RR on appropriate catalystsurfaces.…”
Section: Co 2 Activation and Competitionreactionsmentioning
confidence: 97%
See 3 more Smart Citations